A phenomenological analysis of masculinity ideologies among college males - Gale, Steven R., author; Rickard, Kathryn M., advisor; Viney, Wayne, committee member; Cropanzano, Russell, committee member; Zimmerman, Toni, committee member (Colorado State University. Libraries, 1999)
It was argued that use of qualitative methodology, rather than continued use of extant quantitative measures, is necessary in order for current masculinity ideologies to be fully documented. The 245 male, undergraduate student participants completed the Male Role Norms Inventory (MRNI) of Levant et al. (1992) and the Gender Role Conflict Scale of O'Neil et al. (1986). Of these, 29 also participated in an in-depth interview designed to elicit their experiences of masculinity ideology. Constant comparative analysis of the interview data revealed two core relevant themes. The first theme was that these students did have a consistent understanding of the masculinity ideology that they held for themselves and observed in society. Although this ideology corresponds highly to extant descriptions of masculinity ideology, there were also important differences. These differences included characteristics of nurturing others and expressiveness, at least in the context of one's family, that have typically been attributed solely to feminine ideology. The second theme was that these students also experienced ambivalence and uncertainty about the demands of this ideology. These results support the conclusion that these men are struggling with some changes in the traditional masculinity ideology. The data are also consistent with constructionist theories of gender which assert that differences in masculinity ideologies between groups are attributable to differences in status within society rather than differences in culture. It is suggested that future research include participants from a wider demographic range. It is also suggested that the interviews themselves would provide an ideal source from which to draw items for a more current quantitative measure of masculinity ideology.
Keywords: social psychology; personality; personality psychology